Economic, political and cultural cooperation in Caucasus and central Asia - International ADAM Conference 2010 : Baku, Azerbaijan); Bulut, Mehmet, 1970-.; Aydin, Recai ([Ankara] : ADAM, 2011)
Caucasus; economic conditions; 21st century; congresses.
Includes bibliographical references.
Keywords: Kafkasya -- Ekonomik koşullar -- 21. Yüzyıl -- Kongreler; Caucasus -- Economic conditions -- 21st century -- Congresses; Politikası ve hükümet -- 1991- -- Kongreler; Caucasus -- Politics and government -- 1991- -- Congresses; Asia, Central -- Foreign relations -- Turkey -- Congresses; Asya, Merkez -- Dış ilişkiler -- Türkiye -- Kongreler